ACUTE TOXICITY STUDY OF ARSENICUM ALBUM IN WISTAR ALBINO RATS - A., MONISHA; S., BHUVANESHWARI; S., VELARUL; A. T., SATHIYA VINOTHA; M. S., UMAMAGESWARI; A., VIJAYAMATHY; T. M., KARTHIKEYAN (International Journal of Pharmacy and Pharmaceutical Sciences, 2024)
Objective: In India, homeopathic medicines derived from arsenic trioxide, such as Arsenicum album (A. album), are used to treat COVID-19. Many of the Arsenicum album's adverse events during the COVID treatment led to drug discontinuation. Nonetheless, Ayurvedic, Yoga and Naturopathy, Unani, Siddha, and Homoeopathic (AYUSH) medicine prescribes it. Researching Arsenicum album's toxicity is now essential since it will help decide whether or not the drug can be utilized during treatment. Methods: Acute oral toxicity was performed in Wistar Albino Rats to find out the effects of Arsenicum album in various organs. Rats were divided into three groups: Group A (control), Group B (Arsenicum album 1000μl/100g) and Group C (2000μl/100g). A Single bolus dose of Arsenicum album was given orally and the study period was conducted for 14 d. The rats were subsequently sacrificed on the 15th d and biochemical and histopathological studies were done. Results: The acute oral toxicity study showed median Lethal dose (LD50) was greater than 2000μl/100g for Arsenicum album. Biochemical analysis showed a significant increase in HDL level in Group C (2000μl/100g) compared to Group A (control) and Group B (1000μl/100g). [P<0.05]. Blood glucose, when compared to Group A (control) is increased in both groups B and C but statistically not significant (p>0.05). When compared to Group A (control) there is no significant change in blood urea level in Groups B and C (p>0.05). Serum creatinine is increased in Groups B and C compared to Group A (control) but statistically not significant (p>0.05). LDL cholesterol is increased in groups B and C compared to Group A (control) but statistically not significant (p>0.05). Macroscopic examination of the organs of Group B and C revealed no abnormalities when compared with the organs of Group A (control). Histopathological analysis showed mild hepatocellular and renal toxicity in Groups B and C with extensive hemorrhages and periportal lymphocytic infiltrates.